Laparoscopic versus open varicocelectomy comparative study for early post-operative complications among patients in Basrah, Iraq - Ali, Alaa H.; Alhilfy, Hussain A.; Alharoon, Mahmood S. (International Surgery Journal, 2018)
Background: Varicocele is considered a major cause of male infertility. The target of varicocele surgery is to remove the progressive harmful effect of the varicocele on the testes. The aim of this study was to evaluate post-operative complications of laparoscopic versus open varicocelectomy. Methods: This prospective study involved 60 patients who presented to Al-Basra general hospital, or Al-Sader teaching hospital complaining of pain, infertility, or both and diagnosed to have testicular varicocele. Patients were split into 2 groups relative to the type of operation. Group 1 comprised 25 patients who had undergone laparoscopic varicelectomy, and group 2 comprised 35 patients who had undergone open subinguinal varicelectomy. Results: The mean age of the patients was 25.3±2.1 years in group 1 and 24.4±3.4 years in group 2. Wound infection, hematoma formation, and scrotal edema occurred in the study groups but were higher for open technique. Conclusions: Author concluded in this study that it seems to be laparoscopic varicocelectomy technique has less early post-operative complication in term of wound infection, hematoma and edema.